A Review of the Dose Justification of Phase 3 Trials to Regulatory Authorities for Drugs Intended for the Treatment of Type 2 Diabetes in Europe - Koomen, Jeroen V.; Stevens, Jasper; Monster-Simons, Margje H.; Heerspink, Hiddo J. L.; Mol, Peter G. M. (Frontiers in Pharmacology, 2021)
Aims Cardiovascular outcome trials with anti-diabetic drugs suggest that additional cardiovascular benefit can be achieved independent of improving glycaemic control. Nonetheless, dose selection of anti-diabetic drugs is typically based solely on glycaemic effects. We evaluated whether off-target drug effects are currently considered for dose justification to regulatory agencies. Methods In the European Union, anti-diabetic drugs are registered by the European Medicines Agency. We extracted available information regarding dose selection from public assessment reports and marketing application dossiers. Descriptive statistics were used to summarise the extracted information. Results In total, 14 drugs of three drug classes were included; sodium-glucose co-transporter-2 inhibitors (n = 4), dipeptidyl peptidase-4 inhibitors (n = 4) and glucagon-like peptide-1 receptor agonists (n = 6). For these drugs, 21 dose-finding trials were submitted including results of multiple off-target effects, of which body weight (n = 18) and low-density lipoprotein cholesterol (n = 14) were most frequently reported. Dose-response curves for off-target effects appeared to be different compared to the glycaemic dose-response curve. Glycated haemoglobin (HbA1c,100%) and fasting plasma glucose (FPG, 42.9%), were used most frequently used for the dose justification, but generally off-target effects (<25%) were not. Conclusions Dose justification to regulatory authorities was mainly based on glycaemic effects. The dose-response relationship for the off-target effects did not necessarily follow the dose-response relationship of the on-target effects suggesting that selection of the optimal anti-diabetic dose could benefit from including off-target effects in the dose selection process as well.